Enhancing Mobile Application Security using Priguard Model - Anusuya, C.; Parthiban M. E. , R. (International Journal For Research In Advanced Computer Science And Engineering, 2016)
Permissions-based safety model of Android progressively shows its weakness in shielding users confidentiality information. Permitting to the permissions-based security model,an application should have the suitable permissions before ahead various possessions in the mobile. This model can only control an application to access system funds without appropriate permissions, but cannot prevent malevolent admissions to privacy files after the application having obtained permissions. During the installation of an application, the system will swift what permissions the application is requesting. Users have no optimal but to allow all the entreated authorizations if they want to use the application. Once an application is effectively fitted, the system is ncapable to regulator its activities with dynamism, and at this time the application can acquire confidentiality information and send them out lacking the responses of users. Therefore, there is a great security threat of the permissions-based security ideal. This paper explores on different ways to contact users privacy information and suggests a outline named PriGuard for with passion protecting users privacy information based on Binder communication capture technology and feature selection algorithm. Applications customarily call system services slightly by using the Binder mechanism, then contact the implements and obtain information through system facilities.